Karakteristik Rasm dalam Manuskrip Mushḥaf Al-Qur’an KH. Abdul Hamid Chasbullah - Rif’atul Khanin Mahfudzoh; Adrika Fithrotul Aini; Salamah Noorhidayati (Studia Quranika, 2024)
One of the Qur'an manuscripts from the 20th century is the written version (mushḥaf) KH. Abdul Hamid Chasbullah. The mushḥaf is evidence of the historical heritage of the ulama of Nusantara who have special attention in the field of copying the Qur'an manuscripts. In this study, the author will examine the general description of the mushḥaf and the characteristics of the rasm by referring to the rules of Sheikh Jalal Al-din Al-Suyuthi in the book Al-Itqan fi Ulum Qur'an. The method that the author uses is qualitative research that leads to library research, by using observation tools, interviews, and documentation of the manuscript. The findings of this study are first, this mushḥaf is kept intact (not scattered) although some sheets have been lost and eaten by termites. This 32.3 x 21 x 7.5(cm) mushḥaf was written for the personal use of the copyist. It can be seen that there aren’t illustration and illumination aspects. Second, from the analysis of surah Al-Baqarah juz 2, the copying of this mushḥaf still adheres to the basics of mixed rules between the rasm utsmani and imla'i. Likewise, in terms of qira'at, this mushḥaf mostly uses the history of Imam Hafs 'an Ashim, but some words use mixed history.